Teacher talk: An empowering resource for EMI teachers across disciplines - Kanoksilpatham, Budsaba - (Studies in English Language and Education, 2025)
The increasing demand for English-Medium Instruction (EMI) in universities faces significant challenges, particularly with instructors limited English proficiency impacting speech intelligibility. This study has the goal of exploring the role of teacher talk as a resource to empower 49 Thai EMI university instructors across seven disciplines. Instruments employed included teacher talk as core training materials for the Thai EMI teachers, a pretest and posttest associated with teacher talk for assessing word stress perception and production, a satisfaction survey to evaluate participants feedback on the training, and a focus group discussion to gather qualitative insights on their experiences. The methodology involved a documentary investigation identifying 20 essential teacher talk functions, from which 80 key multisyllabic words were extracted. These words formed the basis for pretest and posttest assessments administered at the trainings start and end. The training emphasized explicit instruction on accurately producing these key words and sentences related to the 20 functions. Following the training, the participants completed the posttest, a production task involving teacher talk utterances, a satisfaction survey, and a focus group discussion. Results revealed a significant increase in test scores, demonstrating the trainings effectiveness in enhancing the participants word stress knowledge. A team competition-based production task further validated their ability to apply these skills practically. Additionally, a mean perception score of 4.62 and positive feedback from the participants provided strong evidence of the trainings success. The study underscores the value of teacher talk as a training resource, highlighting its potential to empower EMI educators across various disciplines for successful classroom instruction.